An Introduction to Animal Husbandry in the Tropics - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
J A Payne & R T Wilson, Blackwell Science. 1999.ISBN 0 632 04193 5.£85.00 Euro 132.80(See Blackwell Science,reference for address p. 13)